Redirecting soluble antigen for MHC class I cross‐presentation during phagocytosis. Issue 2 (8th December 2014) - Hari, Aswin; Ganguly, Anutosh; Mu, Libing; Davis, Shevaun P.; Stenner, Melanie D.; Lam, Raymond; Munro, Fay; Namet, Inana; Alghamdi, Enaam; Fürstenhaupt, Tobias; Dong, Wei; Detampel, Pascal; et al.
<x xml:space="preserve">Abstract</x> Peptides presented by MHC class I molecules are mostly derived from proteins synthesized by the antigen‐presenting cell itself, while peptides presented by MHC class II molecules are predominantly from materials acquired by endocytosis. External antigens can also be presented by MHC class I molecules in a process referred to as cross‐presentation. Here, we report that mouse dendritic cell (DC) engagement to a phagocytic target alters endocytic processing and inhibits the proteolytic activities. During phagocytosis, endosome maturation is delayed, shows less progression toward the lysosome, and the endocytosed soluble antigen is targeted for MHC class I cross‐presentation. The antigen processing in these arrested endosomes is under the control of NAPDH oxidase associated ROS. We also show that cathepsin S is responsible for the generation of the MHC class I epitope. Taken together, our results suggest that in addition to solid structure uptake, DC phagocytosis simultaneously modifies the kinetics of endosomal trafficking and maturation. As a consequence, external soluble antigens are targeted into the MHC class I cross‐presentation pathway.